2020
DOI: 10.3892/ol.2020.12222
|View full text |Cite
|
Sign up to set email alerts
|

Pseudolaric acid B induces apoptosis in human rhabdomyosarcoma RD cells

Abstract: Pseudolaric acid B (PAB) is a diterpene-type acid isolated from the root and trunk bark of Pseudolarix kaempferi Gordon of the Pinaceae family that has been demonstrated to induce apoptosis in various cell lines and autophagy in certain cell lines including murine fibrosarcoma L929, human thyroid squamous cell carcinoma SW579 and human lung fibroblast MRC5 cells. However, in human rhabdomyosarcoma RD cells, which are derived from the most common soft tissue sarcoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Immunofluorescence staining of MRC-5 cells was performed as previously described ( 41 ). MRC-5 cells plated onto cover glasses were fixed with 4% paraformaldehyde for 15 min and then blocked in 5% BSA for 1 h both at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence staining of MRC-5 cells was performed as previously described ( 41 ). MRC-5 cells plated onto cover glasses were fixed with 4% paraformaldehyde for 15 min and then blocked in 5% BSA for 1 h both at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…In short, PAB exhibits a strong parasiticidal effect on E. multilocularis larvae both in vitro and in vivo. Previous study demonstrated that PAB exerts antitumor effects by activated apoptosis, autophagy and cell cycle arrest in certain types of cancer cells (Yu et al, 2008, Liu et al, 2020a. It was recognized that TGF-β1 signaling could trigger a variety of cellular responses, including inhibition of cell growth, migration, differentiation and apoptosis (Sanchez-Capelo, 2005).…”
Section: Groupmentioning
confidence: 99%